STRATEGI PEMASARAN DALAM MENINGKATKAN PENJUALAN KOMODITI DI KANTOR PERUM BULOG MAUMERE - Hubertus Noventino Manis; Nunsio Handrian Meylano; Viktor Eko Transilvanus (Universitas Nusa Nipa Maumere, 2026)
The State Logistics Agency (Bulog) plays a strategic role in maintaining national food security by stabilizing the prices and availability of staple food commodities. Amidst increasingly fierce market competition and changing consumer behavior, the Maumere branch of Bulog faces challenges in increasing commercial commodity sales without neglecting its public function. This study aims to analyze the marketing strategy implemented by Bulog Maumere to increase food commodity sales, as well as identify obstacles and improvement efforts. Using a descriptive qualitative approach through observation, interviews, and documentation, the findings indicate that Bulog Maumere's marketing strategy integrates the 4Ps of the marketing mix—product, price, place, and promotion—through expanded distribution channels (RPK, traditional markets, government agencies), market operations (SPHP, the Affordable Food Movement), and collaboration with local partners. This strategy is effective in increasing sales volume and accelerating stock turnover, although it remains hampered by reliance on government assignments, lengthy bureaucratic procedures, and distribution delays. Key recommendations include strengthening commercial sales, optimizing digital marketing, and improving operational efficiency. The results of this study provide a practical contribution to the development of marketing strategies for public food institutions in the archipelago.